Technical Efficiency of Sugar Industry in Sudan: Stochastic Frontier Approach (University of Khartoum Engineering Journal, 2022)
This paper employs Stochastic Frontier Analysis (SFA) to estimate technical efficiency of major sugar producers in Sudan, that includes Kenana Sugar Company and four producers of Sudan sugar company (SSC) which include Sennar, Assalaya, New Halfa, and Al-Genied manufacturers. The production function of sugar output employs three inputs: capital, labor, irrigated area. The finding of the paper indicate technical inefficiency (distance from optimum production frontier) of Sudan sugar company is about 8 percent, implying output loss of (5,000) tons of sugar per annum for each producer. Estimation results in the paper also indicate Kenana Sugar Company is performing at the highest level of efficiency in the group with only 0.12 percent inefficiency level. The output loss due to such technical inefficiency for Kenana Sugar Company is estimated 360 tons of sugar per annum. The finding in the paper also indicate a major source of the inefficiency of SSC producers is over staff of employment (decreasing return to scale to labour input) and under utilization of the available capital inputs (increasing return to scale to capital input).